REPLIKASI PERPUSTAKAAN ROLE MODEL PENINGKATAN LITERASI INFORMASI UNTUK PEMBERDAYAAN PEREMPUAN DI DESA BOJANEGARA KECAMATAN SIGALUH KABUPATEN BANJARNEGARA PROVINSI JAWA TENGAH - Budi Handari (Ikatan Pustakawan Indonesia, 2019)
Library replication is an information literacy improvement program for women’s empowerment in Bojanegara Village, Sigaluh District, Banjarnegara District, Central Java Province. Activities carried out include improving the quality of human resources and infrastructure assistance. In order to find out and describe the perceptions and motivations of female librarians for library replication programs in the location villages, this study uses quantitative descriptive methods. Collecting data other than through questionnaires, interviews were also conducted using interview guides. To analyze the data, used the Relative Distribution Frequency Method and Cross Tabulation Analysis. The results showed that the perception and motivation of female readers influenced the implementation of librarian replication programs.